Види робочого часу поліцейських - Сіротов, О. А.; Sirotov, O. A. (Юридичний вісник. - 2022. - № 5. - С. 361-367, 2022)
Розкрито особливості правового регулювання робочого часу поліцейських. Запропоновано класифікацію режимів робочого часу працівників органів та підрозділів Національної поліції України. Окреслено особливості та проаналізовано окремо кожний вид робочого часу, який має місце у сфері трудової діяльності поліцейських. Наголошено, що положення відомчого законодавства про діяльність поліції, незважаючи на їх основоположний характер не надають належного уявлення про те, яким саме чином виділяються різні види робочого часу.

The relevance of working time can take a different form not only depending on its physical, time indicator, but also other parameters, for example, a specific period of the day or profession. Thus, the regime of working hours varies according to the work of police officers, as a result of which there are special varieties of the specified category that do not always correlate with the general types of working hours established at the level of labor legislation as a whole for other categories of employees. The article reveals the specifics of the legal regulation of police officers’ working hours. The classification of working time regimes of employees of bodies and units of the National Police of Ukraine is proposed. The peculiarities of each type of working time, which takes place in the field of police work, are separately analyzed. It is emphasized that the provisions of departmental legislation on police activity, despite their fundamental nature, do not provide a proper idea of how exactly different types of working time are allocated. On a general basis, there is a fiveday working week for the entire police force. At the same time, the legislator also uses the term “special conditions” on the basis of which types of service are distinguished in specific periods of time and under certain circumstances. In this case, according to the logic of things, these “conditions” are the corresponding varieties of working (duty) time of police officers, because they establish the grounds for which the normal duration and mechanism of work of employees of the National Police of Ukraine changes. It was concluded that, unlike many other categories of employees, the work of the police provides several types of working hours at once, which are determined by special state tasks and functions entrusted to the National Police of Ukraine by legislation. At the same time, one of the most controversial in the list of types of working hours of police officers is “service with an irregular schedule”, the meaning of which is not explained in any way in the departmental legal framework, as are the features of other types. Because of this, the correction of the normative provisions with the establishment of a new, more perfect and in accordance with the provisions of the Labor Code classification of types of working time of policemen should be accompanied in parallel by the definition of the characteristics of each of the types.

Раскрыты особенности правового регулирования рабочего времени полицейских. Предложена классификация режимов рабочего времени работников органов и подразделений Национальной полиции Украины. Обозначены особенности и проанализированы отдельно каждый вид рабочего времени, который имеет место в сфере трудовой деятельности полицейских. Отмечено, что положения ведомственного законодательства о деятельности полиции, несмотря на их основополагающий характер, не дают должного представления о том, каким образом выделяются различные виды рабочего времени.
Types of working hours of police officers
Сіротов, О. Види робочого часу поліцейських / О. Сіротов // Юридичний вісник. - 2022. - № 5. - С. 361-367. - DOI: https://doi.org/10.32782/yuv.v5.2022.41.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; поліцейські; police officers; полицейские; робочий час; working hours; рабочее время; правове регулювання; legal regulation; правовое регулирование; класифікація робочого часу поліцейських; classification of working hours of police officers; классификация рабочего времени полицейских